2018
DOI: 10.14233/ajchem.2018.21473
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High Performance Conductive Polyaniline Magnetite (PANI/Fe3O4) Nanocomposites by Sol-Gel Method

Abstract: The conductivities of polyaniline magnetite (PANI/Fe3O4) nanocomposites prepared by sol-gel method were measured by standard van der Pauw DC 4-point probe method. PANI/Fe3O4 conductivity was measured as a function of wt % (5, 10, 15, 20 and 25 wt %) of Fe3O4 nanoparticles. It was observed that the conductivity of polyaniline containing certain percentage of Fe3O4 nanoparticles is slightly lower than the bulk PANI nanotubes and drastically decreases with increase of wt % Fe3O4 nanoparticles. The high conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…3 a and b . The images attained using FE‐SEM shows the predominantly spherical‐shaped particles with high aggregation, this may be due to the strong inter‐particle's Van der Waals force and magnetic attraction among the Fe 3 O 4 NPs [54]. The chitosan was strongly bound on the surface of the hybrid Chi‐Fe 3 O 4 nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…3 a and b . The images attained using FE‐SEM shows the predominantly spherical‐shaped particles with high aggregation, this may be due to the strong inter‐particle's Van der Waals force and magnetic attraction among the Fe 3 O 4 NPs [54]. The chitosan was strongly bound on the surface of the hybrid Chi‐Fe 3 O 4 nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…It takes five hours of milling process of local agriculture waste to reduce the material size to nanoscale during synthesis, and powder form was agglomerated [109]. Various milling parameters on nanosilicon found that micron-sized silicon was reduced to nanosilicon with 78 nm at 20 h and good rheological dispersion behaviour in fluid [110]. Agriculture waste was synthesised with additional HCl and reasonable milling time at a speed of 22 rpm for 15 min as an alternative for cement concentre [111].…”
Section: Mechanochemical High Energy Ball Mill (Hebm)mentioning
confidence: 99%
“…eggshell component, which present on the outer surface of the prepared hybrid nanocomposite. The presence of O and Mg signals are due to the protein compounds that are unbound and adhered with the nanostructure, which were removed by centrifugation followed by repeated washing [25][26][27]. The weak signals of C and Ca may be from the eggshell component.…”
Section: Synthesis and Physicochemical Characterizations Of Fe 3 O 4 /Pva/eggshell Hybrid Nanocompositementioning
confidence: 99%